IMPLIKATUR PERCAKAPAN DALAM IKLAN ROKOK DI SIARAN TELEVISI SWASTA NASIONAL - Hapizah Hapizah; Mangatur Sinaga; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: This study titled is Implicature Conversation on Cigarette Advertisements on National Private Television Broadcast. This study aims to describe the type of implicature, and the implicit speech functions contained in cigarette advertisement on national private television broadcast. This research’s type was a descriptive-qualitative research. The data were obtained by uninvolved conversation observation method, recording technique, and note taking. The method of data analysis used is research qualitative method. To test the validity of the data used reference collection and discussion. The results of this research show that, first, the type of implicature in cigarette advertisement on national private television broadcast, that is a) general conversation implicature b) special conversation implicature and b) conventional implicature; second, the function of the implies implies in the cigarette national private television broadcast, that is a) statement, b) information, c) quip, d) advised and e) invited.Key Words: Implicature, The Implicit Speech Functions, Cigarette Advertisement